2023
DOI: 10.1039/d2cp05581c
|View full text |Cite
|
Sign up to set email alerts
|

1D group V–VI–VII ternary nanowires: moderate band gaps, easy to exfoliate from bulk, and unexpected ferroelectricity

Abstract: One-dimensional nanowires have emerged as compelling ideal materials due to characteristic structure, properties, and applications in nanodevices. Herein, based on experimental vdW-chain bulk crystals, a serious of one-dimensional (1D) XVYVIZVII...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…It can be found that the hole mobilities of the 1D NbS 4 nanowire is 316.63 cm 2 V À1 s À1 , which is larger than other 1D materials, such as Nb 2 Se 9 (2.5), 22 Ta 2 Ni 3 Se 8 (42.9), 23 X V Y VI Z VII (X = As, Sb, and Bi; Y = S, Se, and Te; Z = Cl, Br, and I) (ranging from 5.25 to 27.29), 27 InSeI (54.17), 96 Sn 2 S 3 (33.9) and Sn 2 Se 3 (309.1), 83 SbSeI (6.84) and SbSI (23.41) as well as SbSBr (0.64). 95 And the electron mobility of 1D NbS 4 nanowire is 111.9 cm 2 V À1 s À1 , which is larger than that of most reported 1D materials, such as Nb 2 Se 9 (41.9), 22 Ta 2 Ni 3 Se 8 (59.6), 23 most of X V Y VI Z VII (X = As, Sb, and Bi; Y = S, Se, and Te; Z = Cl, Br, and I) (ranging from 16.43 to 322.95), 27 Sn 2 S 3 (63.5), Sn 2 Se 3 (85.9), 83 SbSeI (25.69), SbSI (54.55), SbSBr (96.68), 95 and InSeI (27.49). 96 Furthermore, the carrier mobility of the 1D NbS 4 nanowire exhibits obvious anisotropy, manifesting that the hole mobility is approximately three times larger than the electron mobility.…”
Section: The Stability Electronic Structure and Optical Properties Of...mentioning
confidence: 87%
See 2 more Smart Citations
“…It can be found that the hole mobilities of the 1D NbS 4 nanowire is 316.63 cm 2 V À1 s À1 , which is larger than other 1D materials, such as Nb 2 Se 9 (2.5), 22 Ta 2 Ni 3 Se 8 (42.9), 23 X V Y VI Z VII (X = As, Sb, and Bi; Y = S, Se, and Te; Z = Cl, Br, and I) (ranging from 5.25 to 27.29), 27 InSeI (54.17), 96 Sn 2 S 3 (33.9) and Sn 2 Se 3 (309.1), 83 SbSeI (6.84) and SbSI (23.41) as well as SbSBr (0.64). 95 And the electron mobility of 1D NbS 4 nanowire is 111.9 cm 2 V À1 s À1 , which is larger than that of most reported 1D materials, such as Nb 2 Se 9 (41.9), 22 Ta 2 Ni 3 Se 8 (59.6), 23 most of X V Y VI Z VII (X = As, Sb, and Bi; Y = S, Se, and Te; Z = Cl, Br, and I) (ranging from 16.43 to 322.95), 27 Sn 2 S 3 (63.5), Sn 2 Se 3 (85.9), 83 SbSeI (25.69), SbSI (54.55), SbSBr (96.68), 95 and InSeI (27.49). 96 Furthermore, the carrier mobility of the 1D NbS 4 nanowire exhibits obvious anisotropy, manifesting that the hole mobility is approximately three times larger than the electron mobility.…”
Section: The Stability Electronic Structure and Optical Properties Of...mentioning
confidence: 87%
“…1D and deformation potential constant E 1 , the total energies and band dispersion in the 1D nanowire under a series of small strains are calculated. For the elastic constant C 1D obtained through curve fitting, there is only one elastic constant C 11 = 2.26 Â 10 À8 J m À1 for the 1D NbS 4 nanowire, which is larger than those of the 1D Nb 2 Se 9 , 22 X V Y VI Z VII (X = As, Sb, and Bi; Y = S, Se, and Te; Z = Cl, Br, and I),27 SbSI and SbSBr95 but slightly smaller than those of 1D Ta 2 Ni 3 Se 8 , 23 Sn 2 X 3 (X = S and Se)83 and SbSeI 95. Obviously, the 1D NbS 4 nanowire is mechanically stable because of meeting the Born criterion of C 11 4 0.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…29 In theory, Peng et al 30 suggested that 1D SbSI nanowires thinner than 7 Å are dynamically and thermally stable, and can potentially be highly desirable in next-generation FETs because they enable an appropriate band gap, effective mass, and static dielectric constant. Similarly, Zhang et al 31 found that one-dimensional X V Y VI Z VII (X = As, Sb, Bi; Y = S, Se, Te; Z = Cl, Br, I) ternary nanowires possess excellent stability. Chen et al 28 experimentally synthesized one-dimensional single-crystalline SbSI microrods at 160 1C, and a high-stability photodetector device was fabricated and demonstrated.…”
Section: Introductionmentioning
confidence: 84%
“…14 Such Janus monolayers, characterized by artificial mirror and inversion asymmetry, represent a burgeoning class of materials that show some novel phenomena. [15][16][17] For example, the 2D Janus Sn 2 SSe monolayer demonstrates an evident increase in spontaneous polarization (4.81 Â 10 À10 C m À1 ), compared to 2D SnS (2.62 Â 10 À10 C m À1 ) and SnSe monolayers (1.51 Â 10 À10 C m À1 ). 18,19 Similarly, the 2D Janus Ge 2 SSe monolayer exhibits a larger absorption coefficient of 5.8 Â 10 5 cm À1 than the 2D GeSe monolayer (B10 5 cm À1 ).…”
Section: Introductionmentioning
confidence: 99%